External validation of Pentafecta in patients undergoing laparoscopic radical cystectomy: results from a high-volume center - Li, Kai; Yang, Xiao; Zhuang, Juntao; Cai, Lingkai; Han, Jie; Yu, Hao; Zhou, Zijian; Lv, Jianchen; Feng, Dexiang; Yuan, Baorui; Wu, Qikai; Li, Pengchao; et al. (BMC urology, 2022)
To investigate whether Pentafecta is suitable for bladder cancer patients receiving laparoscopic radical cystectomy (LRC). From November 2013 to December 2020, muscle invasive Bladder Cancer (MIBC) and non-muscle invasive Bladder Cancer (NMIBC) patients who received LRC and urinary diversion were retrospectively analyzed. Pentafecta was defined as meeting five criteria: negative soft margin, ≥ 16 lymph nodes (LNs) removed, major complications free, urinary diversion related sequelae free and clinical recurrence free within 1 year. Analyze the achievement of five criteria and compare the overall survival (OS) of Pentafecta group with non-attainment group. Multivariable Cox's regression was performed to evaluate the impact of Pentafecta on OS. Multivariable logistic regression was performed to explore the effect of surgical experience on Pentafecta attainment. A total of 340 patients were included, negative soft margin, ≥ 16 lymph nodes (LNs) removed, major complications free, urinary diversion related sequelae free and clinical recurrence free within 1 year were observed in 95.3%, 30.3%, 83.8%, 75.0% and 85.6% of patients, respectively. Pentafecta group had a significantly longer OS than the non-attainment group (P = 0.027). The group with 10-15 LNs removed and meeting the other four criteria had a similar OS to group with ≥ 16 LNs removed (Pentafecta group) (5-year OS: 67.3% vs 72.7%, P = 0.861). Pentafecta (HR = 0.33, P = 0.011), positive lymph nodes (HR = 2.08, P = 0.028) and MIBC (HR = 3.70, P < 0.001) were all significant predictors of OS in multivariable Cox's regression. Surgical experience (OR = 1.05, P < 0.001), conduit (OR = 2.09, P = 0.047) and neobladder (OR = 2.47, P = 0.048) were all independent predictors of Pentafecta attainment in multivariable logistic regression. Pentafecta is suitable for bladder cancer patients receiving LRC and has the potential to be a valuable tool for evaluating the quality of LRC. Based on Pentafecta analysis, removing 10 LNs instead of 16 LNs as the one of the five criteria may be more appropriate for bladder cancer patients.